2017
DOI: 10.2217/rme-2016-0171
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes in Japan Towards Human–Animal Chimeric Embryo Research Using Human Induced Pluripotent Stem Cells

Abstract: When presented with a graded view of human-swine chimeric embryo research with concomitant, specific objectives, a large majority of the general public as well as researchers are willing to accept this research with the aims of disease study, novel drug and treatment development, and transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
1
15
2
Order By: Relevance
“…Compared to Kantor's findings, the results of this survey showed a high level of support for the production of HACEs and human-animal chimeras. The acceptance rates were higher than those of a survey conducted by Inoue and his colleagues (referred in Kantor) for the general public and researchers in Japan with respect to the production of HACEs with the purpose of producing organs for transplant [2,3]. One possible reason for this difference is that the subjects were asked about their level of acceptance for various steps: HACE research was classified into three steps and the research objectives of each step were explained in detail (Supporting Information).…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Compared to Kantor's findings, the results of this survey showed a high level of support for the production of HACEs and human-animal chimeras. The acceptance rates were higher than those of a survey conducted by Inoue and his colleagues (referred in Kantor) for the general public and researchers in Japan with respect to the production of HACEs with the purpose of producing organs for transplant [2,3]. One possible reason for this difference is that the subjects were asked about their level of acceptance for various steps: HACE research was classified into three steps and the research objectives of each step were explained in detail (Supporting Information).…”
contrasting
confidence: 57%
“…Between February and April 2016, we conducted a survey on HACE research (Supporting Information) [2]. Regarding the production of HACEs, 81.0% of the public and 92.4% of researchers indicated support.…”
mentioning
confidence: 99%
“…Interestingly, a 2016 survey conducted in Japan of both the general public and researchers showed that more than 60% of the public and 83.8% of researchers supported the creation of human-pig chimeras and 81.0% of the public and 92.4% of researchers supported research on human-pig chimeric embryos [10]. In contrast, the term "person" is a normative-legal, moral, or ethical-term, which refers to a moral and/or legal status that creatures or other bearers of human-like capacities can share with normal humans.…”
Section: Ethical Concernsmentioning
confidence: 99%
“…Transforming animals into human organ donors necessitates experimentation, procedures and genetic modification that might be harmful, deleterious and distressful to the animals. Interestingly, a 2016 survey conducted in Japan of both the general public and researchers showed that more than 60% of the public and 83.8% of researchers supported the creation of human-pig chimeras and 81.0% of the public and 92.4% of researchers supported research on human-pig chimeric embryos [10]. Most likely, the potential that xenograft technology can help save human life may justify the use of animals in this venture.…”
Section: Ethical Concernsmentioning
confidence: 99%
“…The recent revision of the guidelines permits researchers to produce and use HACEs for basic research and disease modeling and for an alternative for organ transplantation in the future. Our survey results revealed that although the Japanese public is generally supportive of the production of human-animal chimeras, they are very concerned about the contribution of human cells into the brains and gametes of animals (Sawai et al, 2017a(Sawai et al, , 2017b. So if researchers would like to pursue the production of chimeric animals with humanized brains and human gametes, public ethical debates should be conducted.…”
mentioning
confidence: 99%